Eulipidemic Effects of Berberine Administered Alone or in Combination with Other Natural Cholesterol-lowering Agents - Cicero, Arrigo F. G.; Rovati, Lucio C.; Setnikar, Ivo (Arzneimittelforschung, 2007)
Berberine (BERB) and a combination (COMB) of berberine (CAS 2086-83-1) with policosanol (CAS 557-61-9), red yeast extract (containing monacolin, CAS 557-61-9), folic acid and astaxanthin were orally administered daily for 4 weeks to 40 subjects with moderate dyslipidemias divided in two parallel groups each of 20 subjects. Total cholesterol (TC), LDL, HDL, Non HDL, ApoB, ApoA, Lp(a) and triglycerides (TG) were measured before and at the end of treatments. BERB and COMB significantly reduced TC (respectively by 16% and 20%), LDL (by 20% and 25%), ApoB (by 15 % and 29 %) and TG (by 22 % and 26%), and increased HDL (by 6.6% and 5.1 %). Adverse events or impairments of liver transaminases or of CPK were not observed.In conclusion, food supplements containing natural products such as berberine, policosanol, red yeast extracts, folic acid and astaxanthin could be a useful support to diet and life style changes to correct dyslipidemias and to reduce cardiovascular risk in subjects with moderate mixed dyslipidemias.
Keywords: Berberine; CAS 557-61-9; CAS 2086-83-1; Food supplements; Hypercholesterolemia; Hypertriglyceridemia; Monacolin; Policosanol